Lobster Population Parameter in Bumbang Bay, Central Lombok [Parameter Populasi Lobster Perairan Teluk Bumbang, Lombok Tengah] - Yonvitner Yonvitner; Zulhamsyah Imran; Sulaeman Martasuganda; Beni Osta Nababan; Fransiskus Mao Tokan; Septian Dwi Cahyo; Rifki Aldi Ramadhani (Jurnal Ilmiah Perikanan dan Kelautan, 2019)
AbstractBumbang bay is one of the lobster fishing areas in Central Lombok District, where fishing is carried out at all times and has the potential to disrupt the sustainability of the population in the future. Data is collected from the stock of lobster stocks that are still in fishing cages. Potential risks and fishing pressure could be assessed through length and weight, growth, structure size and potential recruitment analysis. The results of the study found 6 species of lobsters, of which are 2 dominant species were pearl lobster (45.5%) and sand lobster (44.5%) of the total catch. The Length and weight relationship have a negative allometric pattern which is (pearls lobster b = 2.04 and sand lobster = 1.2). The growth rate is relatively slow with a growth rate coefficient of 0.2-0.49 per year. Therefore, recruitment per biomass from the population is also low and exploitation rate about 0.6. The population growth and recruitment relatively low and increasing the exploitation rate, potential to unsustainable of the lobster population in the future.AbstrakPerairan Teluk Bumbang adalah salah satu pusat perikanan lobster di Lombok Tengah, dimana penangkapan dilakukan setiap waktu dan berpotensi mengganggu keberlanjutan populasi dimasa yang akan datang. Potensi risiko dan tekanan penangkapan dapat dikaji melalui analisis panjang dan bobot, pertumbuhan, struktur ukuran dan potensi recruitment. Hasil penelitian ditemukan sebanyak 6 jenis lobster, dimana 2 jenis dominan yaitu lobster mutiara (45,5%) dan lobter pasir 44,5% dari total tangkapan. Hubungan panjang dan berat memiliki pola allometrik negatif (lobster mutiara b=2,04 dan lobster pasir =1,2). Pertumbuhan tergolong lambat dengan koefisien laju pertumbuhan 0,2-0,49 per tahun. Begitu juga recruitment per biomass dari populasi juga rendah dan eksploitasi tergolong tinggi yaitu 0,6. Kemampuan tumbuh yang lambat dengan recruitment yang rendah serta eksploitasi tinggi, potensial menganggu keberlanjutan populasi lobster dimasa yang akan datang.